Evaluation of the Cross-Sectional Area of the Median Nerve by Ultrasonography in Patients With Carpal Tunnel Syndrome - Gholamreza Shamsaei; Leila Behzadinia; Davood Kashipazha; Davood Shalilahmadi; Shooka Mohammadi (Acta Medica Iranica)
The use of ultrasonography (US) as a non-invasive method to evaluate and diagnose musculoskeletal disorders has increased in recent years. This cross-sectional study assessed the cross-sectional area (CSA) of the median nerve using US in patients with carpal tunnel syndrome (CTS). Clinical and demographic data of patients were recorded. Nerve conduction studies (NCS), US, and needle electromyography (EMG) were performed. In addition, US evaluated the flattening ratio (FR) and CSA of the median nerve. This study assessed 600 wrists of 300 patients with CTS referred to Golestan Hospital (Ahvaz, Iran) for nine months. There were 102 males and 198 females, with a mean age of 46.83±9.50 years. Many patients were aged 40-59 years old. Furthermore, 240 patients had bilateral CTS. The hands affected by CTS were categorized into three groups based on the severity of CTS: mild (298 hands, 49.7%), moderate (164 hands, 27.3%), and severe (138 hands, 23%). Substantial differences were detected in the average age, CSA of the median nerve, body mass index (BMI), ring-finger method (RF), FR, and outcomes in Tinel's sign and Phalen's test based on the severity of CTS (P<0.05). The increase in CSA of the median nerve was related to the severity of CTS. In addition, the US could effectively evaluate the severity of CTS. Utilizing US to measure the CSA of the median nerve was beneficial for identifying and assessing the severity of CTS. However, it should not be regarded as a substitute for NCS. Integrating NCS, US, and needle EMG can enhance diagnostic accuracy and provide more comprehensive insights into severity and underlying causes of CTS. These findings may help healthcare professionals prioritize and improve the quality of diagnosis, treatment, and care for patients with CTS.